Gender differences in the risk and protective factors of marijuana use among U.S. College students. (June 2022) - Park, Sung-Yeon; Yun, Gi Woong; Constantino, Nora; Ryu, So Young
Gender differences in the risk and protective factors of marijuana use among college students were explored by analyzing online survey responses from 464 undergraduates. Women perceived higher risk and used marijuana less than men, with no gender difference in peer disapproval. In addition, women had higher objective knowledge regarding the health effects of marijuana, although they exhibited lower confidence in their knowledge. In subsequent regression analyses, health knowledge, confidence in knowledge, perceived risk, and peer disapproval predicted women's marijuana use, whereas only confidence in knowledge and perceived risk predicted men's use. These findings can help devise effective intervention strategies.